Impactos antropogênicos definem traços funcionais da ictiofauna em riachos neotropicais de primeira ordem. - Pereira, Lucas Milani (2016)
More preserved environments show greater values of functional diversity, once more heterogeneous habitats and more food resource variety determine the presence of higher diversity of traits. We investigated the relation between stream fish species traits and environmental characteristics to observe possible distribution pattern mediated by environmental filters. We found that different kinds of land use around streams influence the functional diversity. Moreover, we recorded different distributions of the functional traits according to human impacts. Environmental parameters, such as water velocity and stream width, antagonistically correlated with both compression and ventral region depression indexes. We also observed a positive correlation of water velocity with the functional traits: mouth and head size, and mouth and eye position. These functional traits (related to the feeding habits and habitat use) indicate possible resources partitioning, enabling the co-occurrence of species. Urban land use and the high conductivity were correlated to both, functional traits of detritivorous species and internal fertilization, which allowed the dominance of Poecilia reticulata in urban streams. The conservation of fish diversity in Neotropical streams demands reasonable landscape occupancy, aiming to avoid the reduction of the functional traits variability keeping the species richness and ecosystems functions of this environment.